Comparative Analysis of Production Results and Farming Costs of Tuber Shallots and True Shallot Seed (TSS) in the Off-Season of Sandy Coastal Land - Ismarlin, Ina Fitria; Shoyfiyah, Safira (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The decline in shallot production was caused by low seed quality in quantity and price. One of the government's efforts to overcome the problem of shallot productivity is by using True Shallot Seed (TSS) seeds. This research aimed to determine the comparison of production results and farming costs for tuber shallot and True Shallot Seed (TSS). This research was conducted in Parangtritis Village, Kapanewon Kretek, Bantul Regency. The research method used was comparative with a sample of 14 tuber shallot farmers and 33 TSS shallot farmers. The sample in this study was selected using a saturated sampling technique. The research results show that the average production of tuber shallot and TSS in the off-season on sandy coastal land is 475 kg/1000 m2 and 398 kg/1000 m2. A comparison of the production results of tuber shallot and TSS using SPSS shows Sig. (2-tailed) of 0.597 > 0.05, which means there is no significant (real) difference between the average production of tuber shallot and TSS. The cost of farming TSS shallots during the off-season on sandy coastal land is Rp. 7,106,500, while farming tuber shallot is Rp. 9,427,000. This shows that the costs of farming TSS shallots are cheaper than the costs of farming tuber shallots. Based on this research, it is necessary to increase the role of extension workers and the independence of farmers in developing tuber shallot and TSS shallot farming, which is more prospective to be cultivated in the off-season on sandy coastal land.